2021
DOI: 10.1371/journal.pone.0253862
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of subtrochanteric fracture fixation using short cephalomedullary nails: A finite element analysis

Abstract: A finite element analysis was performed to evaluate the stresses around nails and cortical bones in subtrochanteric (ST) fracture models fixed using short cephalomedullary nails (CMNs). A total 96 finite element models (FEMs) were simulated on a transverse ST fracture at eight levels with three different fracture gaps and two different distal locking screw configurations in both normal and osteoporotic bone. All FEMs were fixed using CMNs 200 mm in length. Two distal locking screws showed a wider safe range th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The Young’s modulus and Poisson’s ratio were applied to each moiety using previously published data in the literature. ( Table 2 ) ( Kumaresan et al, 1999 ; Kim et al, 2020 ; Kwak et al, 2021 )…”
Section: Methodsmentioning
confidence: 99%
“…The Young’s modulus and Poisson’s ratio were applied to each moiety using previously published data in the literature. ( Table 2 ) ( Kumaresan et al, 1999 ; Kim et al, 2020 ; Kwak et al, 2021 )…”
Section: Methodsmentioning
confidence: 99%
“…Despite this, a recent randomized controlled trial and biomechanical studies have demonstrated that for fractures with less than 3 cm of subtrochanteric extension, short nails resulted in comparable outcomes with long nails. [16][17][18] Pertrochanteric fracture in the setting of a capacious proximal canal (type C proximal femoral canal as defined by Dorr et al 19 ) is another factor which has been raised as a possible indication for long-nail selection because of concern for lack of stability and nail toggle; however, this has not been borne out in the literature. 20 The authors prefer to use short nails when possible.…”
Section: Modern Implant Designmentioning
confidence: 99%
“…Despite the advantages of these computational techniques, there are still limited publications relating to studies of the biomechanical behaviors of intramedullary nails in subtrochanteric fractures in the femur. Most of them focus on intramedullary nailing of femoral shaft fractures [14][15][16][17], and very few articles specifically address subtrochanteric fractures [18][19][20][21]. Kwak DK et al [18], Jang CY et al [19], and Lee WC et al [20] presented different works related to the study of the application of short cephalomedullary nails for the treatment of subtrochanteric and intertrochanteric fractures using finite element models.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them focus on intramedullary nailing of femoral shaft fractures [14][15][16][17], and very few articles specifically address subtrochanteric fractures [18][19][20][21]. Kwak DK et al [18], Jang CY et al [19], and Lee WC et al [20] presented different works related to the study of the application of short cephalomedullary nails for the treatment of subtrochanteric and intertrochanteric fractures using finite element models. Kwak DK et al [18] and Jang CY et al [19] investigated the stresses around the nails and cortical bones to determine the most appropriate type of short cephalomedullary nail for different fracture levels.…”
Section: Introductionmentioning
confidence: 99%